2012
DOI: 10.1117/12.913286
|View full text |Cite
|
Sign up to set email alerts
|

High-power disk and fiber lasers: a performance comparison

Abstract: The Performance of High Power Disk Lasers and Fiber Lasers along with their rapid development to the high power cw regime have been of great interest throughout the last decade.Both technologies are still in the focus of several conferences, workshops, and papers and represent the "state-of-the-art" of industrial high power solid state lasers for material processing. As both laser concepts are considered to be the leading 1 µm light-source, this presentation presents an objective and fair comparison of the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 13 publications
(13 reference statements)
0
10
0
Order By: Relevance
“…reported a solid-state laser with a 200µm power delivery fiber which provides output NA of 0.1, and also a fiber laser with 50 or 100µm power delivery fiber which provides output NA of ~0.08 [6]. Langner et al reported a very large-mode-area fiber laser with 5 mm*mrad BPP, which is then free-space coupled to 200µm power delivery fiber and the output NA is 0.065 [7].…”
Section: Ligft Sourcementioning
confidence: 97%
See 1 more Smart Citation
“…reported a solid-state laser with a 200µm power delivery fiber which provides output NA of 0.1, and also a fiber laser with 50 or 100µm power delivery fiber which provides output NA of ~0.08 [6]. Langner et al reported a very large-mode-area fiber laser with 5 mm*mrad BPP, which is then free-space coupled to 200µm power delivery fiber and the output NA is 0.065 [7].…”
Section: Ligft Sourcementioning
confidence: 97%
“…Computer Power meter 2) Power delivery fiber of MM solid-state/fiber lasers For high power applications, such as cutting and welding, laser power of few hundreds to KWs and brightness with beam propagation parameter (BPP) of 2-10mm*mrad is often used [6].…”
Section: Ligft Sourcementioning
confidence: 99%
“…In this way it is easy to generate laser radiation with diffraction limited beam quality. The principle of the double clad fiber is often used to enable the use of inexpensive diode lasers with relatively poor beam quality for optical pumping 1 . With this method, the pump radiation is conducted in an own, larger fiber core, which is arranged concentrically around the actual laser core.…”
Section: Dual Side Pumped Fiber Laser Oscillatormentioning
confidence: 99%
“…[1,2]. In recent years, due to the rapid development of large mode area (LMA) fiber, several research groups have accomplished output power of up to kilowatt level in the continuous-wave (CW) regime [3][4][5][6][7][8][9]. In fact, the majority of these reported high-power fiber lasers belong to a category of randomly polarized lasers.…”
Section: Introductionmentioning
confidence: 99%